ANALYTICAL METHODS PADA PERANCANGAN STRATEGIS SISTEM INFORMASI DAN TEKNOLOGI INFORMASI - Windi Irmayani (Universitas Bina Sarana Informatika, 2016)
Dinas Cipta Karya, Tata Ruang dan Kebersihan Kubu Raya, West Kalimantan experienced some operational problems due to lack of budget, facilities and human resources. These problems can be solved by the development of information systems and information technology (IS/IT) is appropriate . Because the IS / IT can reduce operational costs and maximize existing human resources. It is necessary for the strategic design of the IS / IT analytical methods, such as SWOT, Value Chain, PEST, Five force Model, Mc Farlan and Trend Technology. By analyzing the internal and external business systems and IS / IT internal and external, this study resulted in strategic recommendations IS business, strategic recommendations management / IT, IT strategic recommendations, and portfolio of applications that can help employees work more effectively and efficiently.